Influência de condições de cultivo na formação de células persisters em Acinetobacter calcoaceticus-baumanni - Donamore, Bruna Kern (2016)
Acinetobacter calcoaceticus-baumannii complex opportunistic human pathogens are responsible for several diseases affecting specially intensive care units and immunocompromised patients. These bacteria may also present the persistence phenotype, where a small population of susceptible bacteria survives after a high antimicrobial concentration treatment – which the fraction of surviving cells may be affected by environmental conditions present in the medium. Thus, the aim of this study was to evaluate the influence of oxygen availability and galactose, sodium citrate and sheep blood presence in the formation of these cells upon meropenem and tobramycin exposure. For this, 10 clinical isolates, sent by the Clinical Pathology Laboratory of São Lucas Hospital, had their susceptibility characterized regarding the minimum inhibitory concentration (MIC) to tobramycin and meropenem. The influence of different environmental conditions was analyzed by exposing late exponential-phase cultures to meropenem and tobramycin for 48 h in the presence of sodium citrate, galactose and sheep blood; or in aerated or static condition. For all evaluations, aliquots were removed at determined time points, followed by serial decimal dilutions and drop plating technique on nutrient agar, to estimate the fraction of surviving cells. Aerated condition promoted a reduction of persister cells fraction – independent of antimicrobial used –, and, in addition, concentrations of tobramycin higher than 10X MIC provided even lower levels of these cells after 48 h of treatment. Regarding the presence of different sources of nutrients, it was observed that sodium citrate presence in 48 h of meropenem treatment promoted lower fraction of surviving cells when compared to this same antibiotic associated with galactose; whereas tobramycin exposure in the presence of galactose provided a reduced formation of persister cells in the first 6 h of treatment. Sheep blood, however, did not affect the fraction of surviving cells after 48 h of treatment, independently of the antimicrobial used. A remarkable heterogeneity in the behavior of all 10 isolates used in the study was present, regardless the conditions that have been exposed. Thus, it is possible that the conditions imposed in the experiments have influenced in the formation of persister cells by enhanced production of reactive oxygen species, and through the availability of more targets for antibiotic action by the bacterial growth stimulation.